Balanced Scorecard: Model Pengukuran Kinerja PT. Daya Cipta Perdana - Rizky Marlina Putri; Herlina Pusparini; Yusli Mariadi (Valid: Jurnal Ilmiah, 2023)
This research aims to determine the performance of the model balanced scorecard as a measurement of company performance PT. Daya Cipta Perdana is reviewed from four perspectives, namely a financial perspective, a customer perspective, an internal business process perspective and a learning and growth perspective. This research is a type of qualitative research with a descriptive approach. This study uses primary data and secondary data with several data collection methods including interviews, questionnaires, literature and documentation. The results of this study can be concluded that PT. Cipta Perdana has a good performance. Specifically, performance measurement shows very good value for the customer perspective, internal business process perspective, and growth and learning perspective. From a financial perspective it is considered good because some of the financial ratios measured have decreased every year. This can be seen from PT. Daya Cipta Perdana which is included in a company that carries out project-based sales so that it affects financial reports.